Securing Healthcare Data Exchange Based on Fog Computing and Blockchain Technologies - Jawad, Muwafaq; A. Yassin, Ali; Ali Abed AL-Asadi, Hamid (Iraqi Journal for Electrical and Electronic Engineering, 2026)
IoHT has several benefits for real-time smart healthcare, but because of its limited processing power, storage capacity, and self-defense capabilities, security issues are growing. Although newer blockchain-based authentication solutions have strong security features due to their tamper-resistant decentralized architecture, they come with a high resource cost, requiring a lot of processing power, more storage, and time-consuming authentication procedures. As such, these difficulties provide barriers to reaching the ideal levels of scalability and temporal efficiency, which are essential for the efficient functioning of large-scale, time-sensitive IoHT systems. To solve these challenges, this paper presents an authentication approach designed especially for IoHT systems. Our work consists four-phase process, which includes setting, registration, login and authentication, and HERs Exchange data. To enhance both efficiency and scalability, the proposed scheme employs a combination of 3-D map dimensions chaotic-based public key cryptosystems, and blockchain-based, fog computing technologies and IPFS. We simulate the proposed work to implement health electronic record (HER) by the Ethereum platform and solidity language, the simulation experiments were tested using the JMeter tool. Showed that the key generation time for chaotic-based is faster than (ECC)—furthermore, the average latency ≈ 3.7 ms. A security analysis of the proposed scheme was implemented by the Scyther tool. The formal security analysis demonstrated that the proposed scheme is secured against potential attacks and supports the scalability of the IoHT system.